Adoption versus abandonment of CASE tools: lessons from two organizations - Rahim, Mahbubur; Khan, Khaled; Hasan Selamat, Mohd. (Emerald Publishing, 1997)
In recent years, computer-aided software engineering tools (CASE) have emerged to provide automation support to the software development process. Such automation is a revolutionary progress which promises dramatic improvement in software quality and productivity. However, despite such promises, CASE tools have not proved to be effective in some organizations owing to the fact that far fewer efforts are expended by organizations on evaluation for selection and introduction of appropriate CASE tools. Proposes a conceptual model on CASE environment that is assembled from two distinct but related processes : “CASE selection” and “CASE adoption”. Further argues that CASE adoption process will be affected if an organization fails to select appropriate CASE tools. Therefore, the success of CASE adoption is very much dependent on the process of CASE selection. Moreover, there is also a possibility that even a suitable CASE tool may not contribute positively, if it is not adopted systematically. Thus, if the CASE adoption fails then a CASE environment would not function. Against this background, cites two case studies describing the experiences of two organizations that adopted a particular brand of front-end CASE tool. One organization was successful in introducing the tool, and experienced considerable improvement in quality and productivity. Conversely, the same CASE tool failed to achieve its purpose in another organization. In the light of the model, further describes why and how CASE failed in one organization, and was considered successful in another. Finally, also highlights the lessons learned from their experiences.